Rice Growth Response to Drought Simulation Treatment Using PEG - Annisa Khaira; Zulyusri Zulyusri; Afifatul Achyar; Dwi Hilda Putri; Yusni Atifah; Violita Violita (Bioscience, 2023)
Rice is the main food source for Indonesians. The demand for rice to meet people's needs increases every year due to population growth and efforts to improve nutrition by the community. One of the problems that can affect rice production is drought. Drought is an environmental condition when plants do not get enough water to grow and develop optimally, which can cause a decrease in rice production. To find out how rice growth responds to drought, a study was carried out by giving drought simulation treatments using polyethylene glycol (PEG) on several rice varieties. This study used a completely randomized design that was arranged in a factorial manner with two factors. The first factor was the rice varieties (Harum, Situbagendit, Rosna) the second factor was 0% and 20% PEG concentration. The data obtained were then analyzed statistically using a two-way ANOVA test, and if the results were significantly different, then proceed with Duncan's test at the 5% level.The results showed that the drought simulation treatment had a negative effect on rice growth. Drought simulation treatment using 20% PEG resulted in a decrease in Kadar air relatif (KAR), root length, plant height, and root dry weight of rice. The highest decrease in KAR was found in the sensitive rice variety (Rosna), which was 43.42%. The highest average root length (7.99 cm) was on the sitabaendit variety, and the lowest (5.61) was on the rosna variety. The highest average crown height (17.32 cm) and the lowest (6.61) were on the rosna variety.